2021
DOI: 10.1007/s11356-021-14286-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID-19 cases using bidirectional LSTM on multivariate time series

Abstract: To assist policymakers in making adequate decisions to stop the spread of the COVID-19 pandemic, accurate forecasting of the disease propagation is of paramount importance. This paper presents a deep learning approach to forecast the cumulative number of COVID-19 cases using bidirectional Long Short-Term Memory (Bi-LSTM) network applied to multivariate time series. Unlike other forecasting techniques, our proposed approach first groups the countries having similar demographic and socioeconomic aspects and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Passing univariate inputs into these LSTM variants makes the models prone to overfitting, which in turn deteriorates the model performance on the test dataset. For instance, Said et al, (2021) also observed a reduced performance of Bi-LSTM against Basic LSTM in Qatar, where they looked into multivariate time series data enriched with data related to lockdown measures. While there are several LSTM results available, a direct one-to-one comparison with this study would be fallacious due to the varying locations, model architectures and time period considered.…”
Section: Resultsmentioning
confidence: 99%
“…Passing univariate inputs into these LSTM variants makes the models prone to overfitting, which in turn deteriorates the model performance on the test dataset. For instance, Said et al, (2021) also observed a reduced performance of Bi-LSTM against Basic LSTM in Qatar, where they looked into multivariate time series data enriched with data related to lockdown measures. While there are several LSTM results available, a direct one-to-one comparison with this study would be fallacious due to the varying locations, model architectures and time period considered.…”
Section: Resultsmentioning
confidence: 99%
“…It is adopted to learn from the framework providing better understanding from the learning context ( Abdollahi et al, 2021 ). As BiLSTM is a multivariate time series it allows multiple time series dependent which can be designed together to predict the correlations along with the series recorded or captured variables varying simultaneously over time period ( Said et al, 2021 ). BiLSTM is a deep learning models for the sequential prediction without much error ( Shahid et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A novel support vector regression model was developed to predict the spread, growth rate, and end of the COVID‐19 across different countries (Yadav et al., 2020 ). The bidirectional long‐short term memory was also compared with other state of the art forecasting technique and found to be more effective (Said et al., 2021 ). Three artificial neural network algorithms, Radial Basis‐Function, Fuzzy Cluster‐Means, and Non‐linear Autoregressive‐Network with Exogenous Inputs were used to spatial forecast COVID‐19 cases in Iraq (Yahya et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%